2021
DOI: 10.3389/fmicb.2021.654692
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Small Molecule, LCG-N25, Inhibits Oral Streptococcal Biofilm

Abstract: Dental caries is a chronic oral infectious disease caused by cariogenic biofilm adhered on the tooth surface. Our previous study demonstrated that a repurposed natural compound napabucasin (NAP) showed good antimicrobial activity against oral streptococcal biofilms. The current study designed a novel small molecule, namely LCG-N25, using NAP as a lead compound, and aimed to investigate its potential as an antimicrobial agent in the control of dental caries. LCG-N25 was designed and synthesized with reference t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…This finding showed that ultrasound irradiation could promote the release of drug from nanoparticles, improve the slow release efficiency, and effectively increase the drug concentration at the local infection site. On the other hand, the nanoparticles themselves could act as exogenous cavitation nuclei, which could enhance the cavitation effect of ultrasound and increase the bacterial biofilm permeability while promoting more drug entry into the biofilm (Yang et al, 2019;Sun et al, 2020;Lyu et al, 2021;. After ultrasound treatment, the penetration of DiI-NPs (DiI as a model drug, fluoresces red) in the biofilm was observed by CLSM.…”
Section: Discussionmentioning
confidence: 99%
“…This finding showed that ultrasound irradiation could promote the release of drug from nanoparticles, improve the slow release efficiency, and effectively increase the drug concentration at the local infection site. On the other hand, the nanoparticles themselves could act as exogenous cavitation nuclei, which could enhance the cavitation effect of ultrasound and increase the bacterial biofilm permeability while promoting more drug entry into the biofilm (Yang et al, 2019;Sun et al, 2020;Lyu et al, 2021;. After ultrasound treatment, the penetration of DiI-NPs (DiI as a model drug, fluoresces red) in the biofilm was observed by CLSM.…”
Section: Discussionmentioning
confidence: 99%
“…The demand for novel antibiofilm agents and the research to explore their molecular mechanism have significantly increased in recent years. For instance, the LCG-N25 is a small molecule and it has been shown to have a potent activity against oral streptococcal biofilm ( 28 ). In this study, we identify a novel small-molecule compound S-342-3 that exerted a strong inhibitory activity against biofilm formation in both MRSA and MSSA clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…LPS was extracted from 5 mL of different Xoo cultures at the same concentration of OD 600 = 0.8 using LPS extraction kit (BestBio Biotechnology Ltd., Shanghai, China). Quantification of LPS was conducted by anthrone-sulfuric method [ 33 ] with modifications. Briefly, the standard curve of saccharide was generated using anhydrous glucose, the extracted LPS (200 μL) was mixed with anthrone reagent (600 μL) (2 g/L anthrone prepared with concentrated sulfuric acid), and then the reaction mixture was heated in a water bath at 95 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%